Larvicidal Anthraquinones and Triterpenes from Ploiarium alternifolium (Theaceae) - Ee, G.C.L.; Ng, K.N. (Asian Journal of Chemistry, 2010)
Chemical studies on the stem bark of Ploiarium alternifolium (Theaceae) have yielded the anthraquinone emodin, and its derivative a methoxy bearing anthraquinone. These 2 compounds have not been reported to be present in this plant. Also isolated from the same plant was ploariquinone, a geranyl anthraquinone. Separation of the triterpenoid-containing fraction gave the phenolic oleanane benzoate. Structural elucidations of these compounds were achieved using 1H NMR, 13C NMR, DEPT, COSY and HETCOR experiments while MS gave the molecular masses. The crude extracts were found to be moderately bioactive against the larvae of Aedes aegypti. This paper reports the isolation and identification of these compounds as well as bioassay data for the crude extracts.